Peningkatan Rasa Persatuan Dan Kesatuan Dalam Membangun Filsafat Pancasila Di SDN Gili Barat - Hikmah Labibah; Dya A'yun (Institut Nalanda, 2023)
The study discussed the implementation of the 3rd pancasila of the west bank to increase unity and unity among students. The implementation of pancasila values is done through activities that teach cultural diversity, build teamwork, and foster tolerance and appreciation for differences among students. The essential role of teachers and parents in instilling the values of unity and unity in students is also taught in this study. The research method used is qualitative descriptive using data collection techniques by observation and interview. Observations indicate that the application of the pancasila values is done through division of students into groups to find solutions to the given problem. Additionally, the study also highlights the problem of integrating the values of unity and unity among students, particularly in class v, and suggests that teachers focus more on organizing classes and maximizing learning to increase the sense of unity and unity among students.